PENGARUH KONTEN DAN AKSES MEDIA ONLINE KOMPAS.COM TERHADAP KEPUASAN INFORMASI MAHASISWA S1 FAKULTAS KOMUNIKASI MERCU BUANA - Mulatua Hasiholan (MediaKom : Jurnal Ilmiah Komunikasi, 2019)
Information is one of human fundamental needs. Nowadays, online media is being such an alternative way to fulfil this need of information. This research aims to examine the influences of news content and access of online media to the information satisfaction of college students. The theory used in this research is cognitive model of Uses and Gratification, which the variables involved are information elements (content and access) as X variable and satisfaction obtained as Y variable. This research was conducted in Mercu Buana University, with total sample about 340 college students. Primary data collecting utilizes questionnaire technique research, where the respondents were requested giving a response based on a whole statement written intended to measure the influence of content and access of Kompas.com as an object of observation. Primary data processing using a quantitative analysis method, specifically with a multiple regression analysis. The results of this research are concluded as follows:(1) Content and access variables together significantly influence the college student information satisfaction with coefficient of determination by 56,2%, (2) Content variable significantly influence the college student information satisfaction by 24%, and (3) Access variable significantly influence the college student information satisfaction by 41,3%. Keywords: content, access, information satisfaction, online media, journalism